2017
DOI: 10.1016/j.otsr.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous posterior fixation for unstable pelvic ring fractures

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…A similar profile of neurovascular abnormalities has been observed in other studies, which have also found that some patients experience osteoarthritis of the proximal sacroiliac joint; therefore, longer periods of follow-up are recommended to monitor long-term complications more efficiently. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…A similar profile of neurovascular abnormalities has been observed in other studies, which have also found that some patients experience osteoarthritis of the proximal sacroiliac joint; therefore, longer periods of follow-up are recommended to monitor long-term complications more efficiently. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…These parameters are particularly relevant for the treatment of polytrauma patients who may be hemodynamically unstable but also for the treatment of more fragile older patients [13,14,26,27]. Thus a transverse construct was proposed by Tempelaere et al [28] and Okuda et al [22], combining an L5 pedicle hold to create a crab-shaped lumboiliac construct. Shah et al [29] recently described a minimally invasive lumboiliac fixation with distal fixation at S2.…”
Section: Discussionmentioning
confidence: 99%
“…Pedicular screws and iliac screws can be inserted percutaneously under fluoroscopy or navigation and the rod inserted with a percutaneous dedicated spine device. These percutaneous procedures may be contraindicated if the reduction is not obtained under traction because of the difficulties to add reduction maneuvers percutaneously ( 31 , 32 ). Percutaneous procedures decrease blood loss and infection rates ( 33 ).…”
Section: Which Surgical Treatment?mentioning
confidence: 99%